2013
DOI: 10.1089/scd.2012.0486
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood-Derived Mesenchymal Stem Cells Inhibit, But Adipose Tissue-Derived Mesenchymal Stem Cells Promote, Glioblastoma Multiforme Proliferation

Abstract: Mesenchymal stem cells (MSCs) possess self-renewal and multipotential differentiation abilities, and they are thought to be one of the most reliable stem cell sources for a variety of cell therapies. Recently, cell therapy using MSCs has been studied as a novel therapeutic approach for cancers that show refractory progress and poor prognosis. MSCs from different tissues have different properties. However, the effect of different MSC properties on their application in anticancer therapies has not been thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 63 publications
6
124
1
1
Order By: Relevance
“…In addition, Zhao and colleagues (57) reported that ASCs chemoattract endothelial cells by a VEGFdependent method. Jeon and colleagues (58) showed that the lysophosphatidic acid (LPA)-LPA1 signaling pathway played a key role in ASC differentiation and VEGF-mediated angiogenesis, Akimoto and colleagues (59) illustrated that ASCs may support glioblastoma multiforme by promoting angiogenesis, and Klopp and colleagues (60) suggested that through expressing various, specific factors, omental ASCs increase tumor vascularization in endometrial cancer.…”
Section: Ascs Promote Angiogenesismentioning
confidence: 99%
“…In addition, Zhao and colleagues (57) reported that ASCs chemoattract endothelial cells by a VEGFdependent method. Jeon and colleagues (58) showed that the lysophosphatidic acid (LPA)-LPA1 signaling pathway played a key role in ASC differentiation and VEGF-mediated angiogenesis, Akimoto and colleagues (59) illustrated that ASCs may support glioblastoma multiforme by promoting angiogenesis, and Klopp and colleagues (60) suggested that through expressing various, specific factors, omental ASCs increase tumor vascularization in endometrial cancer.…”
Section: Ascs Promote Angiogenesismentioning
confidence: 99%
“…But the anti-cancer properties of MSCs in humans are controversial because of still incomplete and limited human studies performed on small number of patients. The proposed use of MSCs in cancer therapies provoke strong disagreement in scientific community, due to opposite results for MSC promotion of tumor vascularization, promotion of cancer progression and the invasive tendency of tumors previously reported [28,[120][121][122]. In this contest, Li et al, 2011, inform about the dual role of human MSCs in tumor cell growth in vitro and in vivo.…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancermentioning
confidence: 97%
“…There is still no confirmation of this hypothesis, and investigations are still in progress as many authors have described cells from the microenvironment which exhibit several differences with their parent cells. In one study [28]. Isolated primary glioblastoma multiforme (GBM) cells are co-cultured with MSCs and their characteristics are analyzed with cotransplantation assays.…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancermentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs have been extracted from several adult human tissues including the connective tissues of all human organs, the bone marrow (BM), skeletal muscle, synovium, dental pulp, and adipose tissues [29][30][31][32][33]. MSCs can also be harvested from fetal tissues such as umbilical cord blood, placenta, amniotic membranes, and amniotic fluid [31,[33][34][35][36][37][38][39].…”
Section: Sources Of Stem Cells -Advantages Disadvantages and Othermentioning
confidence: 99%